Duration of transition into the monad stage as a useful criterium for identification of species within Chlamydomonas (Chlorophyta) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Methods for evaluation of the duration of the transition from vegetative cells to the monade state are described. Duration of the transition state, iniciated by the transfer of cultures from solid to liquid media, corresponds with molecular clades. This was observed on the sample of 12 species presented by 12 authentic strains which belong to 4 different larger clades. Duration of the transition depends on: (1) presence of the flagella in immobile cells, (2) capability to form flagella de novo, (3) presence, solubility and width of mucilage sheaths on surface of vegetative cells in their immobile state.
Keywords: Reinhardtinia, Moewusinia, Oogamochlamydinia, Chloromonadinia, taxonomy, morphology, motile stage.